REALISM OF SINCLAIR LEWIS: SYNCRETIC FEATURES - Aziza Komilovna Akhmedova (Western European Studies, 2024)
The study investigates Sinclair Lewis's characterization techniques from the point of view of the genre. The findings reveal that the writer created romantic heroes in his realistic novels("Arrowsmith", "Godseeker") being influenced by Fenimore Cooper. Most of his antiheroes such as Babbit, Elmer Gantry, and Buzz Windrip are modeled after certain pathological personality disorders which proves that the writer carried a deep sociopsychological investigation in the depiction of the characters. This feature makes him closer to the naturalist authors who research human nature in detail. Though indifferent to modernism, Sinclair Lewis still incorporated some modernistic elements in his novels. The motif of metamorphosis in the novel "Kingsblood Royal reflects the inner transformation of the hero. The syncretic nature of the Realism of Sinclair Lewis provides literary charm to his characters.
Keywords: syncretism; realism; character